2016
DOI: 10.7205/milmed-d-15-00245
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characteristics of Traumatic Shoulder Instability in Japanese Military Cadets

Abstract: Little is known regarding the incidence of the shoulder instability in Japan. The aim of this study was to evaluate the incidence of traumatic shoulder instability among Japanese military cadets. A prospective cohort study was performed to capture all traumatic shoulder instability events between 2009 and 2012 among cadets in a military educational academy of the Japan Self Defense Forces. The total number of cadets in the cohort was 5,402 (average age 20.6 years). The incidence of instability events, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Anterior shoulder dislocations are the primary cause of shoulder instability (SI), a condition that refers to the inability to maintain the humeral head in the glenoid fossa [1]. The incidence of primary shoulder dislocation is 8.2 to 23.9 per 100,000 person-years, and its estimated prevalence is 1.7% [2, 3]. About two thirds of shoulder dislocations will evolve into SI within five years [4].…”
Section: Introductionmentioning
confidence: 99%
“…Anterior shoulder dislocations are the primary cause of shoulder instability (SI), a condition that refers to the inability to maintain the humeral head in the glenoid fossa [1]. The incidence of primary shoulder dislocation is 8.2 to 23.9 per 100,000 person-years, and its estimated prevalence is 1.7% [2, 3]. About two thirds of shoulder dislocations will evolve into SI within five years [4].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies with military populations, the incidence of shoulder joint dislocations is reported to be even higher. [28][29][30] Amako et al 29 reported an incidence of 410 per 100,000 person years among Japanese military cadets, Kardouni et al 30 reported an incidence of 313 per 100,000 person years among U.S. military soldiers, and Owens et al 28 reported an incidence of shoulder joint dislocation as high as 435 per 100,000 person years among U.S. military cadets.…”
Section: Discussionmentioning
confidence: 99%
“…Shoulder dislocation often occurs during high-intensity athletic activities. 9 , 10 The majority of dislocations are anterior and typically occur when sudden forces at the extreme ends of glenohumeral abduction-external rotation are adequate to displace the humeral head anteriorly. 11 The anterior shoulder musculature, namely the pectoralis major, anterior deltoid, biceps brachii, coracobrachialis, and subscapularis are considered dynamic anterior stabilizers of the shoulder and therefore most suited to protect it from anterior dislocation.…”
Section: Introductionmentioning
confidence: 99%